(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The nineteenth century in Europe was marked by the strong women’s movement which was focused on women’s suffrage and political equality. Although most of the movement’s participants and supporters shared the same main goals, their priorities varied among countries, nations and communities. As participants in the national liberation movement, Serbian women believed that their emancipation and achievement of political equality were in the national interest. Using as a reference point several classic works of feminist scholarship, this essay explored various discourses related to the women’s emancipation, “women’s question” and “women’s rights” as they were represented in the women’s journal Žena / Woman. By so doing, the essay tried to show how certain historical and geopolitical contexts affect women’s struggle for equal political rights. Moreover, it emphasized the importance of archival research for establishing and better understanding of the history of Serbian feminist movement.